Peculiarities of Approaches Used in the Process of Students English Language Training - Magdyuk, Olga (Pedagogical Discourse, 2016)
The article deals with the peculiarities of approaches usage in the process of English language studying by students of philological specialties. The essence of cognitive, informational, behavioural, innovative, intuitive, conscious, communicative, individual, «thematic», active and pragmatic approaches was revealed. Focus on the communicative approach as one of the most effective approaches of English learning process was paid. Communicative approach was examined in the light of grammatical competence. It was proved that the choice of methodology and effective approach in the process of foreign languages studying is relevant and reflected in the works of domestic and foreign scientists. However, in spite of this, as shown by the analysis, the constant evolution of theoretical bases of different approaches and their specific implementation in the learning process leads to misunderstanding and problems during their usage. As it can be seen from the experience, the main purpose of students of philological specialities English language studying is to develop communicative competence. The value of this concept becomes clearer and more understandable if to compare it with the concept of grammatical competence. The attention in the process of communicative approach application is paid to group training. The task of the participants of the educational process is to learn to work together, to leave individualized training. Students learn to listen to their friends, communicate and discuss the project in group working with other group members. The communicative approach to teaching also means that the subject of educational activity is in the center of process of learning, and training system provides maximum consideration of individual, psychological, age and national characteristics of a student. The communicative approach in modern methodology is regarded as the theoretical framework of language learning. It exists primarily to remove the fear of communication. Keywords: approach, communicative approach, students of philological speciality, grammatical competence, English language.